An Adaptive Architecture for Autonomic Orchestration of Web Services (International Journal of Engineering and Computer Science, 2017)
Web service is an emerging paradigm in which loosely coupled software components are published, located and invoked on the web as a part of distributed applications. The advantage of employing web service composition is to create and consume a value added service by composing simple and complex software components which are deployed at different locations in an autonomic manner. The centralized web service composition approaches suffer from performance bottleneck and a single point failure. The web services are also distributed across geographical boundaries and they may be constantly removed or upgraded. The solution for the above problem is dynamic composition of web services. The proposed framework can handle any kind of users irrespective of their role in order to utilize the proposed architecture either as a provider or as a consumer. The proposed system performs autonomic composition of web services on-the-fly in order to perform dynamic composition of the services related to each other.